Dyssynchronous Secretory Endometrial Glands Often Show Sporadically Acquired Progesterone Nonresponsiveness. (May 2015) - Howitt, Brooke E.; Monte, Nicolas M.; Elvin, Julia; Mutter, George L.
Abstract : Primary sporadic gene-inactivating events within the progesterone response cascade might explain the presence of individual dyssynchronous (outlier) glands commonly observed in a secretory background. We queried morphologically dyssynchronous glands in mid-secretory endometrium with a series of markers normally downregulated by progesterone. Seventy-nine mid-secretory endometrial biopsies were stained with hematoxylin and eosin, MIB-1, PAX2, estrogen and progesterone receptors, and PTEN. Aberrant staining of glands was independently scored for each marker. Outlier glands overlapping between stains were enumerated. A total of 63% of cases had hematoxylin and eosin stained outlier glands (average 9), which often demonstrated failed progesterone-mediated downregulation of PAX2 (43%), estrogen (40%), and/or progesterone receptors (28%). Aberrations of progesterone response was seen in 70% to 85% of cases overall, averaging 10 to 30 glands/affected case. The frequency and burden of affected glands was similar to that seen for primary inactivating events of the PAX2 and PTEN genes (35% and 41% of cases, respectively, averaging 32 and 38 glands per affected patient). Sporadic gene-inactivating events are common during endometrial regeneration, and may cause morphologic changes unmasked by the hormonal context. Some of these dyssynchronous "outlier" glands, whether evident on hematoxylin and eosin stain or not, have an interrupted progesterone response.